Laporan Tahunan Berbasis Maqasid Syariah - Hananto, Bernad; Masriah, Iin (Jurnal Ekonomi Syariah Pelita Bangsa, 2020)
By revealing the Maqasid Sharia into the annual report, it can be understood that the entity has sharia principles. This study intends to describe the Maqasid Sharia to be an items that is relevant to the business aspects of the Islamic business entity. In this study it was found that the five principles of maqasid sharia can be translated into more detailed items, the principle of guarding religion (hifzh al diin) is how entities play a role in syiar, the spread of religion, sodaqoh / helping fellow human beings and how the mission of the entity is explained in accordance with maqasid sharia, the principle of safeguarding the soul (hifzh al nafs) is where the role of the entity can provide a sense of fairness, comfort, security and fairness and the development of personality, the principle of safeguarding intelect (hifzh al aql) is to play a role in the development of human resources, the principle of safeguarding posterity (hifzh al nasl) is to maintain health, a decent life, preserve human beings also means maintaining the preservation of the environment or ecosystem, so as to ensure the resources of all time, the principle of safeguarding wealth (hifzh al mal) is the principle of how the wealth is acquired / developed and how the wealth is distributed.